If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 9 = 7m + 12 Reorder the terms: 9 + 4m = 7m + 12 Reorder the terms: 9 + 4m = 12 + 7m Solving 9 + 4m = 12 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. 9 + 4m + -7m = 12 + 7m + -7m Combine like terms: 4m + -7m = -3m 9 + -3m = 12 + 7m + -7m Combine like terms: 7m + -7m = 0 9 + -3m = 12 + 0 9 + -3m = 12 Add '-9' to each side of the equation. 9 + -9 + -3m = 12 + -9 Combine like terms: 9 + -9 = 0 0 + -3m = 12 + -9 -3m = 12 + -9 Combine like terms: 12 + -9 = 3 -3m = 3 Divide each side by '-3'. m = -1 Simplifying m = -1
| y^4+2y^2+1=0 | | 2(-5r-6)=-12-6r | | 8x+19=26 | | 4x+2=9-2x | | 4(5x+2)=-24+4x | | 3(k-3)-5=7k-(3k-2) | | f(x)=9xln(7x)-9x | | 2[3-4(5-7)]= | | -3(1r+3)=-1(-6+36) | | (6x+6)(2x^2+4x+4)= | | 9x-12=8x+3 | | -5a-25=5(-2a+4)-4a | | 2cos(x)sin(x)=-sin(x) | | 2m+4n+6m+5n= | | 6.9=9.6 | | y^4-1= | | -6(3p+4)=16+2p | | 3+2(1-3x)=1-2x | | x^10-16= | | 4v=5(v+1) | | X-6=-13/2 | | x^5-80x= | | 1.4x=43.90 | | 7(x+6)=6(x-7)+x | | -83p+7p-5p+5+30= | | -2(3x-2)=4x-16 | | n/9+1=12 | | (4/5)c-8=-36 | | 12x^3+40x^2-32x= | | 2r+5s-18+6r= | | -2=(k/4)-7 | | 3(-6k+3)+2k=-29+3k |